Stress and Anxiety to Viral Epidemics-6 for Medical Students: Psychometric Properties of the Anxiety Measure for the COVID-19 Pandemic - Ahn, Junseok; Lee, Jukab; Hong, Youjin; Park, Jangho; Chung, Seockhoon (Frontiers in Psychiatry, 2021)
The aim of this study was to explore the psychometric properties and validity of Stress and Anxiety to Viral Epidemics-6 items (SAVE-6) among medical students who are at high risk of coronavirus disease 2019 (COVID-19) infection. A total of 212 medical students participated in this online anonymous survey that used SAVE-6, Coronavirus Anxiety Scale (CAS), Generalized Anxiety Disorder-7 items (GAD-7), and Work and Social Adjustment Scale (WSAS). We observed that the single-factor structure model of the SAVE-6 scale showed good internal consistency (Cronbach’s alpha = 0.756) and a good convergent validity with GAD-7 (rho = 0.320, p < 0.001), CAS (rho = 0.229, p < 0.001), and WSAS (rho = 0.278, p < 0.001). The appropriate cut-off score of the SAVE-6 scale was determined as 15 points in accordance with at least a mild degree of generalized anxiety (GAD-7 score of 5) among medical students. In conclusion, the SAVE-6 scale can be applied to medical students as a reliable and valid rating scale to assess anxiety response to the present viral pandemic.